The degree of awareness of the principals of the government high schools in the governorate of Irbid for the management of change and its relation to the effectiveness of these schools - El-Taj, Iman Mohamed Ibrahim (Journal of Educational and Psychological Sciences, 2019)
The study aimed at revealing the degree of awareness of the principals of the governmental secondary schools in Irbid Governorate for the management of change and their relation to the effectiveness of these schools. The researcher used the descriptive approach. In order to achieve the objective of the study, the researcher constructed a questionnaire, , And the results showed that the degree of awareness of high school principals in the governorate of Irbid for change management is high and with a mean (4.01). The order of the fields ranked in descending order according to the level of fields: the field of school administration, reached (4.15) Teaching, Reached (3.96), the regulatory climate field, and was (3.92).obaha grade (high), also showed a strong correlation by (0.86), the degree of awareness of public secondary school principals in the governorate of Irbid to manage change effectively and their relationship to those schools. In the light of the results, a number of recommendations and proposals were presented to raise the level of awareness of change management among high school principals.